2009
DOI: 10.1002/jnr.22245
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic–nonenzymatic cellular antioxidant defense systems response and immunohistochemical detection of MDMA, VMAT2, HSP70, and apoptosis as biomarkers for MDMA (Ecstasy) neurotoxicity

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA)-induced neurotoxicity leads to the formation of quinone metabolities and hydroxyl radicals and then to the production of reactive oxygen species (ROS). We evaluated the effect of a single dose of MDMA (20 mg/kg, i.p.) on the enzymatic and nonenzymatic cellular antioxidant defense system in different areas of rat brain in the early hours (<6 hr) of the administration itself, and we identified the morphological expressions of neurotoxicity induced by MDMA on the vulnerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
(41 reference statements)
2
27
0
Order By: Relevance
“…The other finding was that the MDMA-induced toxicity in chronic-treated rats was more exaggerated than acute-treated rats. Consistent with our study, Riezzo et al showed that MDMA administration in rats caused cell death in the CA1 hippocampus (20). Furthermore, Kermanian et al reported an increase in dark cells in the hippocampus following MDMA administration (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The other finding was that the MDMA-induced toxicity in chronic-treated rats was more exaggerated than acute-treated rats. Consistent with our study, Riezzo et al showed that MDMA administration in rats caused cell death in the CA1 hippocampus (20). Furthermore, Kermanian et al reported an increase in dark cells in the hippocampus following MDMA administration (21).…”
Section: Discussionsupporting
confidence: 92%
“…Administration of MDMA causes rapid intracellular Ca 2+ influx, mitochondrial membrane depolarization and reactive oxygen species (ROS) production (22). It also causes oxidative stress, ROS generation (20) and glutathione (GSH) depletion (23) that lead to neurotoxic effects. It has been shown that GSH depletion causes spatial memory impairment (24).…”
Section: Discussionmentioning
confidence: 99%
“…The international scientific panorama is actually rich with studies aimed to identify markers which can provide more and more accurate information about the time of onset of hypoxic-ischemic brain damage and inflammatory response in heroin-related death. However, data reported by the literature appear fragmentary and contradictory, often concerning experimental studies performed only on animals [29,30]. The histological study of the brain with traditional histochemical techniques can provide relevant data since it is well known that depending on mechanism, severity, and timing of the insult, the distribution and the histological pattern of lesions in the brain changes dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…The histological study of the brain with traditional histochemical techniques can provide relevant data since it is well known that depending on mechanism, severity and timing of the insult, the distribution and the histological pattern of lesions in the brain changes dramatically [5,19]. By means of immunohistochemical techniques applied in studies both on animals and humans, it has been possible to identify in the brain tissue some markers of hypoxic-ischemic damage with reliable and reproducible results [20-23]. …”
Section: Discussionmentioning
confidence: 99%